Fashion : philosophy for everyone : thinking with style - Wolfendale, Jessica, 1973-; Kennett, Jeanette, 1954- (Philosophy for everyone, 2011)
"Most of us realize that fashion is more than just clothes. It's not just about wearing what's in. Fashion influences our judgments of people's taste, politics, sexuality, class, religion, and even their moral character. It can be a medium for technological and social change - changes in fashion may signal economic and political shifts. Yet fashion can also trap us. We can be slaves to fashion if we feel trapped by the roles dictated by the clothes we wear, and we can be slaves to fashion, literally, as in the case of sweatshop workers who make most of the clothes we wear today. This book explores the diverse and sometimes contradictory aspects of fashion in a series of lively, entertaining thoughtful essays from prominent philosophers and writers. Topics include: What is fashion? How do we know what is fashionable? Who decides what's cool and what's not? How is it that clothes shape people the way they do? Why does fashion have the power it does? You won't look at your wardrobe in the same light again!"-- Vydavatelská anotace